Processo de ensino-aprendizagem-treinamento no basquetebol: influência no conhecimento tático processual - Juan Carlos Perez Morales (2007)
The objective of the present study was to observe technical-tactical teachinglearning-training process (T-L-T) in basketball analyzing the applied methodology byteacher-trainers and to identify its influence in the level of efficiency of proceduraltactical knowledge (PTK). The sample of this study was constituted of 40 malebasketball student-apprentices from mini-basket category (10-12 years old),belonging to three groups (A, B and C) that presented different methods of T-L-T.Training sessions was ranked and classified using the protocol developed byStefanello (1999). In order to evaluate student-apprentices' T-L-T, KORA test(Evaluation Guided through Concept) was used. It was developed by Memmert(2002) according to tactical parameters Offer and Guide (OO) and Recognizespaces (RE). The results allowed the following conclusions. It was confirmed that, ingroup A, it was used a T-L-T process that emphasizes situational-global method. Itwas verified that in group "B" the use of situational method and mixed method(denominated analytic-global) prevailed. In group "C" was verified an emphasis inuse of analytic method. Qui-square (X²) calculation in constituent categories ofconditions of tasks parameter (I base individual X²=14,48 p <0,05, combination offoundations X²=56,51 p <0,05, CJ1 X²=45,75 p <0,05 and CJ2 X²=45,8 p <0,05) andin constituent categories of tasks parameter (acquisition of technique X²=23,45 p<0,05, fixation and diversification of technique X²=22,5 p <0,05, application oftechnique X²=10 p <0,05 and competition X²=46,21 p <0,05) determined significantdifferences among groups A, B and C. In level of efficiency of PTK, it was confirmedthat situational method combined with global method used in group "A improvedparameters OO convergent (p=,000) and divergent (p=,000) and RE convergent(p=,000) and divergent (p=,000). Situational method associated with mixed method(analytic-global) utilized in group B, only provided improvement in parameter OOconvergent (p=,005) and divergent (p=,024). Finally, analytic method used in group Calso improved parameter OO convergent (p=,046) and divergent (p=,013).